PENGARUH GENDER DAN VANITY SEEKING BEHAVIOR PADA EKUITAS MEREK ATAS PRODUK BERMEREK PREMIUM - , Imla Novia Rizka; , Ike Janita Dewi Dr, MBA, Ph. D, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is aimed to find out whether gender affects brand equity on premium branded products and vanity seeking behavior affects brand equity for premium branded product significantly. There are five main indicators or dimensions of brand equity. They are brand awareness, brand associations, perceived quality, brand loyalty, and other brand-related assets. The research was conducted in Yogyakarta and found three questions that are not valid and removed for further analysis. The questionnaire used to collect data, with 200 respondents is based on whether or not to have been branded products The results of T test found that the brand equity indicators which are brand awareness, brand association, perceived quality and brand loyalty are equal for women and men. The results of simple linear analysis is vanity seeking behavior has a significant effect on the dependent variable and a positive effect on brand equity which are brand awareness, brand association, perceived quality and brand loyalty of premium branded products.